1995
DOI: 10.1177/028418519503600404
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Double-Contrast Enhanced Porcine Myocardial Infarction

Abstract: MR imaging was performed to investigate whether Gd-DTPA-BMA-induced contrast enhancement of myocardial infarction is counteracted by Dy-DTPA-BMA. Myocardial infarction was induced in 5 pigs. Microdialysate probes were inserted in ischemic and nonischemic myocardium. Gd-DTPA-BMA (0.3 mmol/kg b.w.) and Dy-DTPA-BMA (1.0 mmol/kg b.w.) were administered i.v. 4 hours post occlusion. The microdialysate was collected every 10 min and measured for Gd and Dy using inductively coupled plasma atomic emission spectrometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The reperfused infarctions in the current study contained a 3-fold higher concentration of Gd than did 6-h-old nonreperfused infarctions (mean 0.90, SD 0.16 mmol/kg d.w.), 2 h after Gd injection in a previous study (16). These differences in behavior of contrast media in reperfused and nonreperfused infarctions are believed to be caused by the rapid delivery of contrast medium, with extravasation due to capillary damage and reactive hyperemia during the early stage of reperfusion, compared with a slow diffusion of the contrast agent into the infarction in the absence of reperfusion.…”
Section: Discussionmentioning
confidence: 81%
“…The reperfused infarctions in the current study contained a 3-fold higher concentration of Gd than did 6-h-old nonreperfused infarctions (mean 0.90, SD 0.16 mmol/kg d.w.), 2 h after Gd injection in a previous study (16). These differences in behavior of contrast media in reperfused and nonreperfused infarctions are believed to be caused by the rapid delivery of contrast medium, with extravasation due to capillary damage and reactive hyperemia during the early stage of reperfusion, compared with a slow diffusion of the contrast agent into the infarction in the absence of reperfusion.…”
Section: Discussionmentioning
confidence: 81%
“…Previous investigations using microdialysis clearly established the difference between the tissue concentration of Gd-DTPA-bismethylamide and its extracellular concentration in an occlusive pig infarction model (18). Since loss of cell membrane integrity could frequently occur in ischemically damaged myocardium (13), intracellular accumulation of Gd-DTPA might also be one of the mechanisms of Gd-enhancement in reperfused myocardial infarction.…”
Section: Discussionmentioning
confidence: 96%
“…The tissue Gd-DTPA concentration was measured using inductively coupled plasma (ICP) emission spectrometry (15,17,18,(20)(21)(22). The heart was excised, and the atrioventricular connective tissue and apical part were removed.…”
Section: Tissue Gd-dtpa Concentration and Water Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our data are consistent with uptake of contrast agent by tumor cells, with a gradient of contrast agent concentration from vascular to extra-to intracellular spaces, but with complexity in the mechanisms that allow distribution of the contrast agent into the various tissue compartments. Additional evidence that contrast agents may enter the intracellular space was shown in a study of myocardial infarction with both Gd-and Dy-based contrast agents, where it was observed that susceptibility effects due to contrast agent compartmentation were lower than expected, suggesting distribution of the agent both intra-and extracellularly due to loss of cell membrane integrity (35). It is plausible that some tumor cells may also be in a stage of severe hypoxia with membrane damage prior to necrosis, but still with measurable levels of choline.…”
Section: Effect Of Gd-dtpa On Choline Signalsmentioning
confidence: 94%